Tecnologia da informação aplicada à estratégia de saúde da família: uma nova maneira de realizar a estratificação de risco familiar - Lima, Jefferson Caio (2019)
New technologies have become common in healthcare lately. Their aim is to give a range of healthcare professionals access to information so as to increase the cost- effectiveness of care delivery and to improve the efficacy of care. Nowadays information technology (IT) may be seen as a cornerstone when it comes to solving health systems issues. The objective of this paper was to develop a website to gather data of a specific population in order to apply a familiar risk scale proposed by Coelho and Savassi. The data collected will be helpful in primary care. Health professionals will be able to prioritize home visits and to know better the assisted population. In order to develop the website we used the PHP programming language, the CakePHP framework and MySQL database. These tools were chosen due to their good performance and compatibility. Besides, they are open source code. We developed the website and tested it on a neighborhood assisted by Family Health Strategy. We applied the Coelho-Savassi’s scale to 1623 families. According to their scores, 1148 (70,7%) categorized as common risk; 104 (6,4%), minor risk; 152 (9,4%), medium risk; and 219 (13,5%), maximum risk. Simultaneously we applied the adapted scale in order to compare it with the original one. Statistical data analysis showed significant difference between the two scales, favoring the use of the adaptation on the studied area. We were able to deliver a functional website that seemed to be relevant in this particular setting. Hence were able to apply the proposed scales and stratify the assisted families. This will contribute to prioritize home visits and to plan healthcare according to specific needs of the studied population.